Viga prismática delgada e elástica: três aplicações de importância prática na engenharia - Araújo, Jorge Corrêa de; Marquez, Rosa Garcia (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2024)
Prismatic beams subjected to forces can undergo elastic deformations. In this study, three applications involving an almost straight prismatic steel beam are analyzed. The first consists of a concentrated load P at its midpoint, where the modeling is treated in two different ways. One form uses the bending moment equation with boundary conditions applied at one of its ends and at the center point of the beam. This approach was in good agreement with the model developed in this study, where the boundary conditions are applied at the ends of the beam. In the second application, a spring is placed under the bar at the midpoint, in order to attenuate the vertical movement caused by P force. The elasticity curve of these deformations was determined here. The third application involves the placement of three equidistant loads on the bar to obtain an unforced kinematic representation of this movement.